Peran Notaris Dalam Membuat Akta Perjanjian Notariil - Sumini Sumini (Jurnal Akta, 2017)
ABSTRACTThe agreement is the agreement of both parties to do an act. Agreements are very often used in everyday life, both under contract and notarial agreement. In the contents of the agreement the parties make in accordance with the principle of freedom of contract. Agreement under the hands of frequent problems caused by parties because the strength of the agreement is binding. Therefore, the need of Notary's role in making the notarial agreement deed so that the parties can achieve their respective objectives and secure if one day there will be one of the parties wanprestasi then notariil agreement can be used as legal evidence. The purpose of writing this journal is to know and analyze the role of Notary in making the deed of notarial agreement. The theory used is the theory of legal protection related to notarial agreement deed made Notary can protect the parties in case of dispute or wanprestasi. The method used in the writing of this journal is literature method review books against books related to the theme of the journal that I created and also sourced from several journals from the internet. In making the notarial agreement deed, the notary needs to pay attention to the things that are prohibited in making the agreement, therefore the role of the Notary is very important in the making of Notariil agreement deed.Keywords: Notary's Role, Agreement, Notary Act, Notary ABSTRAKPerjanjian adalah kesepakatan kedua belah pihak untuk melakukan suatu perbuatan. Perjanjian sangat sering digunakan dalam kehidupan sehari-hari, baik perjanjian dibawah tangan maupun perjanjian notariil. Dalam isi perjanjian para pihak membuat sesuai dengan asas kebebasan berkontrak. Perjanjian dibawah tangan sering saja terjadi masalah santar pihak karena tidak kuatnya perjanjian itu mengikat. Untuk itu diperlukannya peran Notaris dalam membuat akta perjanjian notariil agar para pihak dapat mencapai tujuan masing-masing dan aman jika suatu saat nanti ada salah satu pihak yang wanprestasi maka akta perjanjian notariil tersebut dapat dijadikan sebagai alat bukti yang sah. Tujuan dari penulisan jurnal ini adalah untuk mengetahui dan menganalisa peran Notaris dalam pembuatan akta perjanjian notariil. Teori yang digunakan adalah teori perlindungan hukum yang berkaitan dengan akta perjanjian notariil yang dibuat Notaris dapat melindungi para pihak jika terjadi sengketa ataupun wanprestasi. Metode yang digunakan dalam penulisan jurnal ini adalah metode literatur kaji pustaka terhadap buku-buku yang berhubungan dengan tema jurnal yang saya buat dan juga bersumber dari beberapa jurnal dari internet. Dalam membuat akta perjanjian notariil, notaris perlu memperhatikan hal-hal yang dilarang dalam membuat perjanjian, untuk itu peran Notaris sangatlah penting dalam pembuatan akta perjanjian Notariil.Kata kunci: Peran Notaris, Perjanjian, Akta Notariil, Notaris